Question and Answers Forum

All Questions      Topic List

Trigonometry Questions

Previous in All Question      Next in All Question      

Previous in Trigonometry      Next in Trigonometry      

Question Number 203325 by depressiveshrek last updated on 16/Jan/24

sin^2 x+cos^2 (2x)+sin^2 (3x)=(3/2)

sin2x+cos2(2x)+sin2(3x)=32

Answered by esmaeil last updated on 16/Jan/24

sin^2 x+(1−2sin^2 x)^2 +  (3sinx−4sin^3 x)^2 =(3/2)→  sin^2 x+1+4sin^4 x−4sin^2 x+  9sin^2 x+16sin^6 x−24sin^4 x=(3/2)→  16sin^6 x−20sin^4 x+6sin^2 x=(3/2)→  32m^6 −40m^4 +12m^2 −3=0→    4(2m^2 )^3 −5(2m^2 )^2 +6(2m^2 )−3=0  4p^3 −5p^2 +6p−3=0  4p^3 −4p^2 +4p−p^2 +2p−4+1=0  4(p^3 −p^2 +p)−(p−1)^2 −4=0  4(p^3 −p^2 +p−1)−(p−1)^2 =0  4(p−1)(p^2 +1)−(p−1)^2 =0  (p−1)(4p^2 +4−p+1)=0  p=1→2m^2 =1→m=±((√2)/2)→  sinx=sin(±(π/4))→ { ((x=2kπ±(π/4))),((x=2kπ+((3π)/4),x=2kπ+((5π)/4))) :}  4p^2 −p+5=0×

Missing \left or extra \right(3sinx4sin3x)2=32sin2x+1+4sin4x4sin2x+9sin2x+16sin6x24sin4x=3216sin6x20sin4x+6sin2x=3232m640m4+12m23=04(2m2)35(2m2)2+6(2m2)3=04p35p2+6p3=04p34p2+4pp2+2p4+1=04(p3p2+p)(p1)24=04(p3p2+p1)(p1)2=04(p1)(p2+1)(p1)2=0(p1)(4p2+4p+1)=0p=12m2=1m=±22sinx=sin(±π4){x=2kπ±π4x=2kπ+3π4,x=2kπ+5π44p2p+5=0×

Terms of Service

Privacy Policy

Contact: info@tinkutara.com